ADMINISTRATION SYSTEM RENTAL CAR IN PT.XYZ - Mohammmad Budiyanto; Aqwam Rosadi Kadiran, SKom, MM (Jurnal Sistem Informasi, 2005)
Is developing its business in the field of car rental services, which at this CV.XYZ carinformation and data processing customer transactions are processed rental carmanually in the input, processing, and printing to produce a report. By using theapplication program Microsoft Visual Basic 6.0 in form - the form, will facilitate theoperations staff or rental of the administrative officer to perform input, processing,and printing of a good data and customer data due return of car data, and assisted withthe Microsoft database applications Access 2000 for storage of records - record andfield - field data.